PENGARUH ISLAMIC CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN BANK SYARIAH - Tasya Salwa Salsabila Pranandita (2023)
This research is a quantitative study that aims to determine the effect of the implementation of Islamic corporate governance on the financial performance of Islamic banks. Using panel data regression of 13 Islamic banks in Indonesia for the 2018-2020 period. Partially, just independent commissioners has an effect with financial performance. Then, no effect was found between the other ICG components, such as the number of top management, frequency of board of directors meetings, gender diversity, number of sharia supervisory boards (DPS), education level of DPS, frequency of DPS meetings, and concurrent positions of DPS on Islamic bank financial performance. This research provides knowledge for regulators and companies to be able to improve the financial performance of Islamic banks through the implementation of ICG.